(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize current evidence on the efficacy and safety of probiotics, ginger, and black garlic in irritable bowel syndrome (IBS), and to examine the biological rationale and current limitations of combining these components. Methods: This was a narrative review. Core literature was purposively selected from PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar up to 20 November 2025 using terms related to IBS, probiotics, ginger, black garlic, gut microbiota, and gastrointestinal motility. Priority was given to systematic reviews/meta-analyses and randomized controlled trials for probiotics, clinical trials and mechanistic studies for ginger, and preclinical or mechanistic studies for black garlic.. Results: Clinical evidence supports probiotics as an adjunctive option in IBS, with small to moderate benefits on global symptoms and abdominal pain; however, heterogeneity across strains, doses, outcomes, and study design reduces certainty. Human data on ginger remain limited and inconsistent, although tolerability appears acceptable and preclinical studies suggest potential effects on motility, mucosal barrier function, and low-grade inflammation. Evidence for black garlic is indirect and mainly preclinical, suggesting possible modulation of gut microbiota, oxidative stress, and gastrointestinal motility. No clinical trial has directly evaluated a probiotic–ginger–black garlic combination in IBS. Conclusion: Probiotics have the strongest clinical support among the three components. Ginger and black garlic remain promising but insufficiently validated for IBS. At present, combining probiotics with ginger and black garlic should be regarded only as a biologically plausible hypothesis or individualized adjunctive approach, not an evidence-based recommendation.